Weber, Fin De Siecle - Forth, Christopher (Teaching History: A Journal of Methods, 1992)
For many years Eugen Weber has been one of the most prolific and respected American historians studying the Third French Republic. With France: Fin de Siecle, Weber presents a broad but comprehensive view of France during the period he has come to know so well, taking the reader on a tour of the major events and everyday life of this troubled and at times paradoxical era. The result is a well-written and insightful work of history that is accessible, informative, and a joy to read.